(untitled) (Research, Society and Development, 2024)
The study conducted at a public school in Campo Maior, Piauí, aimed to improve the teaching of botany by addressing plant physiology, with a focus on photosynthesis, highlighted as the foundation of the food chain. This area of knowledge, often considered complex and abstract, was approached in a way to facilitate students’ understanding. The research involved two second-year high school classes, using a methodology that combined observation, playfulness, experimentation, and terrarium assembly. The activities began with a walk through the school’s gardens, allowing students to reflect on the characteristics of plants and their role in ecosystems, and culminated in the construction of a food chain. Subsequently, a playful video was used to explain the stages of photosynthesis, followed by practical activities in the science laboratory, where students assembled closed terrariums to consolidate their learning. At the end, a questionnaire was applied to assess the students’ comprehension. The results indicated that most students came to better understand the importance of plants in sustaining life and ecosystems. The study demonstrates that innovative pedagogical approaches, combined with experimental practices, make complex topics more accessible and relevant, fostering meaningful learning in botany.